The Effect of X-Ray and Heavy Ions Radiations on Chemotherapy Refractory Tumor Cells - Yu, Zhan; Hartel, Carola; Pignalosa, Diana; Kraft-Weyrather, Wilma; Jiang, Guo-Liang; Diaz-Carballo, David; Durante, Marco (Frontiers in Oncology, 2016)
Purpose: To link both numeric and structural chromosomal aberrations to the effectiveness of radiotherapy in chemotherapy refractory tumor cells. Materials and methods: Neuroblastoma (LAN-1) and 79HF6 glioblastoma cells derived from patients and their chemoresistant sublines were artificially cultured as neurospheres and irradiated by x-rays and heavy ions sources. All the cell lines were irradiated by Carbon-SIS with LET of 100 keV/µm. 79HF6 cells were also irradiated by Carbon-UNILAC with LET of 168 keV/µm, while LAN-1 cells were irradiated by Nickel ions with LET of 174 keV/µm. The effect of radiation on the survival and proliferation of cells was addressed by standards clonogenic assays. In order to analyze cell karyotype standard giemsa-staining, multicolor fluorescence in situ hybridization technique and multicolor banding technique were applied. Results: Relative biological effectiveness (RBE) values of heavy ions beam relative to X-rays at the D10-values were found between 2.3-2.6 with Carbon-SIS and Nickel for LAN-1, while that were 2.5-3.4 with Carbon-SIS and Carbon-UNILAC for 79HF6 cells. Chemorefractory LAN-1RETO cells were found more radioresistant than untreated LAN-1WT cells. 79HF6RETO glioblastoma cells were found more radiosensitive than cytostatic sensitive cells 79HF6WT. Sphere formation assay showed LAN-1RETO cells were able to form spheres in serum-free culture whereas 79HF6 cells could not. Most of 79HF6WT cells revealed to content 71-90 chromosomes while 79HF6RETO revealed a numeric of 52-83 chromosomes. The majority of LAN-1WT cells revealed a number of 40-44 chromosomes. mFISH analysis showed some stable aberrations especially on chromosome 10 with as judged by the impossibility to label this region with specific probes. This was corroborated using mBAND analysis. Conclusions: Heavy ion irradiation were more effective than X-ray in both cytostatic naive cancer and chemoresistant cell lines. LAN-1RETO chemoresistant neuroblastoma cells were found to be more radioresistant than the cytostatic naive cells (LAN-1WT), whereas this effect was not found in 79HF6 cells.